Quantitative analysis on dietary pattern among year 4 nursing student during clinical and non-clinical posting - Mohamed Ariffin, Suzilawati; Mohd Romaizi, Muhammad Adam Akmal; Che Abdullah, Che Azunie (International Islamic University Malaysia, 2025)
Background: The dietary patterns of Year 4 nursing students at the International Islamic University Malaysia (IIUM) Kuantan campus play a crucial role in shaping their overall health and wellbeing. Nursing students undergo rigorous training that encompasses both clinical and non-clinical postings. The objectives of this study were to assess the eating patterns of Year 4 nursing students during clinical posting and non-clinical postings. Methods: A descriptive cross-sectional study was conducted among 131 nursing students in IIUM, Kuantan. A well-structured questionnaire was used to collect data. Statistical data was analysed by using SPSS. Results: A total of 14 male (10.7%) and 117 female (89.3%) nursing students participated in this study. Their dietary pattern during clinical posting and non-clinical posting had been analysed using Likert scale. Conclusion: There were significant changes in the dietary patterns of students between the two periods. The overall nutritional quality of the diet was lower during clinical postings. The findings suggest a need for better support systems for nursing students during their clinical postings. Ensuring nursing students maintain good dietary habits is crucial not just for their immediate health and academic performance, but also for their long-term well-being and professional effectiveness.